Relationships between δ13C, δ18O and grain yield in bread wheat genotypes under favourable irrigated and rain-fed conditions - Foulkes, M.J.; DeSilva, J.; Gaju, O.; Carvalho, P. (Elsevier, 2016)
In previous investigations, carbon isotope composition (δ13C) has been used in C3 cereals to screen for genotypes with high transpiration efficiency and oxygen isotope composition (δ18O) has been shown to correlate with transpiration rate. We examined associations of δ13C of the grain and flag leaf and δ18O of the flag leaf with respect to grain yield in wheat cultivars in UK field conditions. Field experiments were carried out at University of Nottingham in 2009–10 and 2010–11 testing 17 wheat cultivars under fully irrigated and rain-fed conditions. Averaging across years grain yield was reduced by 1.69 t ha−1 (16.5%) in the rain-fed treatment (P < 0.001). There was a negative linear relationship between grain yield and grain δ13C amongst cultivars, under both irrigated (R2 = 0.47, P < 0.01) and rain-fed (R2 = 0.70, P < 0.001) conditions. Grain δ13C was negatively correlated with flag-leaf stomatal conductance (r = −0.94, P < 0.01) in a subset of six of the cultivars, indicating that higher transpiration efficiency was associated with lower stomatal conductance. The associations between grain yield and flag-leaf δ13C and flag-leaf δ18O amongst cultivars under irrigated and rain-fed conditions were not statistically significant. There was a positive linear relationship between flag-leaf δ18O and grain δ13C amongst cultivars under irrigated conditions (R2 = 0.38, P < 0.01), indicating a trade-off between transpiration and transpiration efficiency (TE). Genetic variation in grain yield under rain-fed conditions was also associated with delayed onset of flag-leaf senescence (R2 = 0.35, P < 0.05). The 17 wheat cultivars ranged in year of release (YoR) from 1964 to 2009 and grain yield increased linearly under irrigated conditions by 60.4 kg ha−1 yr−1 (0.72% yr−1) and under rain-fed conditions by 47.5 kg ha−1 yr−1 (0.66% yr−1) over the 45 year period and grain δ13C composition decreased by 0.0255 and 0.0304‰ yr−1, respectively, indicating genetic gains in wheat yield potential in the UK seem likely to have been achieved through a lower TE, higher water uptake and lesser limitation of stomatal conductance.